2012
DOI: 10.1161/circulationaha.111.080002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Endoglin Activity Limits Cardiac Fibrosis and Improves Survival in Heart Failure

Abstract: Background Heart failure is a major cause of morbidity and mortality worldwide. The ubiquitously expressed cytokine, transforming growth factor beta-1 (TGFβ1), promotes cardiac fibrosis, an important component of progressive heart failure. Membrane-associated endoglin is a co-receptor for TGFβ1 signaling and has been studied in vascular remodeling and preeclampsia. We hypothesized that reduced endoglin expression may limit cardiac fibrosis in heart failure. Methods and Results We first report that endoglin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 43 publications
4
95
0
4
Order By: Relevance
“…Mechanistically, sEng may works through interrupting transforming growth factor-β1 signaling, a pathway that has been previously linked with cardiac fibrosis. 35 Whether sEng is synergistic with sFlt1 in its effects on myocardial function or whether this is an adaptive response is unknown. Placental growth factor levels (a proangiogenic protein) in this cohort did not correlate with cardiac dysfunction (data not shown), suggesting that the driver of the cardiac dysfunction in preeclampsia is likely mediated by antiangiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, sEng may works through interrupting transforming growth factor-β1 signaling, a pathway that has been previously linked with cardiac fibrosis. 35 Whether sEng is synergistic with sFlt1 in its effects on myocardial function or whether this is an adaptive response is unknown. Placental growth factor levels (a proangiogenic protein) in this cohort did not correlate with cardiac dysfunction (data not shown), suggesting that the driver of the cardiac dysfunction in preeclampsia is likely mediated by antiangiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these reports, our present data in the UUO model of tubulo-interstitial fibrosis shows the increase in both Eng mRNA and protein expression in the O kidney ( Figure 1). Several authors demonstrated that Eng promotes fibrosis in different kidney experimental models [15,16,[33][34][35][36][37] and other experimental models of tissue fibrosis in organs such as heart [13,38], liver [39] or skin [40]. Two different Eng isoforms that differs exclusively in the intracellular tail have been reported in both humans [18] and mice [19].…”
Section: Discussionmentioning
confidence: 99%
“…Eng is a TGF-β1 co-receptor that participates in TGF-β1 signaling, and many studies have addressed the involvement of Eng in several fibrotic processes [11][12][13][14][15][16]. Eng is overexpressed in kidneys of patients with chronic kidney disease [17] and in kidneys of animals with several experimental models of renal fibrosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…118). Using human samples, these authors described that endoglin expression is elevated in human failing hearts and that the major source for plasma endoglin was the cardiac fibroblasts.…”
Section: Increased Levels Of Endoglin In Fibrotic Diseasesmentioning
confidence: 99%